2013
DOI: 10.1016/j.drugalcdep.2012.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Striatal D2/D3 receptor availability is inversely correlated with cannabis consumption in chronic marijuana users

Abstract: BACKGROUND Although the incidence of cannabis abuse/dependence in Americans is rising, the neurobiology of cannabis addiction is not well understood. Imaging studies have demonstrated deficits in striatal D2/D3 receptor availability in several substance-dependent populations. However, this has not been studied in currently-using chronic cannabis users. OBJECTIVE The purpose of this study was to compare striatal D2/D3 receptor availability between currently-using chronic cannabis users and healthy controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
41
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 53 publications
8
41
1
Order By: Relevance
“…We also corroborate prior findings (14)(15)(16) of no significant differences in baseline striatal D2/D3 receptor availability between controls and marijuana abusers and provide preliminary evidence of abnormal midbrain DA reactivity in marijuana abusers.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We also corroborate prior findings (14)(15)(16) of no significant differences in baseline striatal D2/D3 receptor availability between controls and marijuana abusers and provide preliminary evidence of abnormal midbrain DA reactivity in marijuana abusers.…”
Section: Discussionsupporting
confidence: 89%
“…Only four brain imaging studies (totaling 42 marijuana abusers) have measured DA D2/ D3 receptors (14)(15)(16)42). These studies showed no differences in striatal D2/D3 receptors between marijuana abusers and controls, but their generalizability is limited by the small sample sizes (samples ranged from n = 6 to n = 16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We included eight case-control studies comparing resting rCBF in adult chronic cannabis users and non cannabis using healthy controls ( [163]. Functional differences between groups were found in all studies, except for the four [ 11 C]-raclopride-PET studies [159][160][161][162]. Abstinence periods ranged from 12 hours to 542 days (for details see Table 2).…”
Section: Structural Neuroimaging Studies In Adolescent Chronic Cannabmentioning
confidence: 99%
“…11 C]-raclopride-PET studies [160][161][162] failed to find any differences between groups in dopamine D2/D3 receptor availability in the striatum as a whole or it functional subdivisions. However, while Stokes [169] used fMRI to compare a visualattention task in current and abstinent cannabis users with healthy controls.…”
mentioning
confidence: 94%